Chemical abundances in Seyfert galaxies, VII : direct abundance determination of neon based on optical and infrared emission lines - Armah, Mark (2021)
For the first time, neon abundance has been derived in the narrow line region from a sample of Seyfert 2 nuclei. In view of this, we compiled from the literature fluxes of optical and infrared (IR) narrow emission lines for 35 Seyfert 2 nuclei in the local universe (z <∼ 0.06). The relative intensities of emission lines were used to derive the ionic and total neon and oxygen abundances through electron temperature estima- tions (Te-method). For the neon, abundance estimates were obtained by using both Te-method and IR-method. Based on photoionization model results, we found a lower electron temperature [te(Ne iii)] for the gas phase where the Ne2+ is located in compar- ison with t3 for the O2+ ion. We find that the differences (D) between Ne2+/H+ ionic abundances calculated from IR-method and Te−method (assuming t3 in the Ne2+/H+ derivation) are similar to the derivations in star-forming regions (SFs) and they are reduced by a mean factor of ∼ 3 when te(Neiii) is considered. We propose a semi- empirical Ionization Correction Factor (ICF) for the neon, based on [Neii]12.81μm, [Neiii]15.56μm and oxygen ionic abundance ratios. We find that the average Ne/H abundance for the Seyfert 2s sample is nearly 2 times higher than similar estimate for SFs. Finally, for the very high metallicity regime (i.e. [12 + log(O/H) >∼ 8.80]) an in- crease in Ne/O with O/H is found, which likely indicates secondary stellar production for the neon.